1999
DOI: 10.1128/jb.181.6.1793-1800.1999
|View full text |Cite
|
Sign up to set email alerts
|

Uracil-Induced Down-Regulation of the Yeast Uracil Permease

Abstract: In Saccharomyces cerevisiae theFUR4-encoded uracil permease catalyzes the first step of the pyrimidine salvage pathway. The availability of uracil has a negative regulatory effect upon its own transport. Uracil causes a decrease in the level of uracil permease, partly by decreasing theFUR4 mRNA level in a promoter-independent fashion, probably by increasing its instability. Uracil entry also triggers more rapid degradation of the existing permease by promoting high efficiency of ubiquitination of the permease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 55 publications
3
44
0
1
Order By: Relevance
“…High substrate concentrations increase the turnover rate of transporters, whereas low substrate availability result in stabilization of the transporters. Previous studies found that the substrate-binding site in Fur4 is required for uracilinduced downregulation, suggesting that Fur4 itself is sensing the presence of uracil, thereby regulating its own turnover rate (2). Furthermore, we found that the presence of both extracelluar as well as intracellular substrate is able to induce internalization and degradation of Fur4 (Figure 3), suggesting that any substratebound state is able to trigger Fur4 ubiquitination.…”
Section: Discussionsupporting
confidence: 62%
“…High substrate concentrations increase the turnover rate of transporters, whereas low substrate availability result in stabilization of the transporters. Previous studies found that the substrate-binding site in Fur4 is required for uracilinduced downregulation, suggesting that Fur4 itself is sensing the presence of uracil, thereby regulating its own turnover rate (2). Furthermore, we found that the presence of both extracelluar as well as intracellular substrate is able to induce internalization and degradation of Fur4 (Figure 3), suggesting that any substratebound state is able to trigger Fur4 ubiquitination.…”
Section: Discussionsupporting
confidence: 62%
“…The number and positions of the MCC patches were shown to be stable (Malinska et al, 2003) and independent of the main cytoskeletal components (Malinska et al, 2004). However, the expression of proteins like Can1p, Fur4p or Tat2p, and consequently their appearance in the plasma membrane, is substrate-regulated (Seron et al, 1999;Kodama et al, 2002). Therefore, these proteins appear in the patches in different amounts and at different times.…”
Section: Discussionmentioning
confidence: 99%
“…We next examined the uracil permease Fur4. This protein has been extensively studied, and it has been shown that the addition of uracil leads to rapid internalization from the cell surface (18). Fur4 is also very sensitive to cycloheximide stress, which similarly results in internalization and vacuolar degradation (19).…”
Section: Multiple Adaptors Control Fur4 Endocytosismentioning
confidence: 99%